Implementation of the Contextual Teaching and Learning (CTL) Approach on the Learning of Moral Beliefs in Madrasah Ibtidaiyah: A Perspective of Axiological Philosophy - Firman Rosyadi, Muhammad; Khoirul Azis, Donny (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Moral beliefs play a fundamental role in student education, as they form a strong moral and spiritual foundation. Learning Moral Beliefs is an effort to increase the understanding and application of moral values in students in daily life. The learning of Moral Beliefs must be adjusted to the material and context of students' lives, so that children can understand and apply it in their daily lives, one of the methods that can be applied is Contextual Teaching and Learning (CTL). This research is a literature review to explore the axiological perspective in the application of Contextual Teaching and Learning (CTL) in Madrasah Ibtidaiyah. Axiology, as a branch of philosophy that discusses values and ethics, emphasizes the importance of instilling moral values in learning. In this context, CTL serves to connect the theory of moral beliefs with the reality of students' daily lives, so that they can internalize and apply these values effectively. The data in this study are literature facts that are accommodated from various theories and previous research results related to the application of Contextual Teaching and Learning (CTL) in learning moral beliefs. The researcher used the interactive analysis method proposed by Miles and Huberman, namely data reduction, data display, and conclusion drawing/verification. Data analysis was carried out by examining the axiological perspective in the implementation of CTL which is integrated in the learning process of Akidah Akhlak. The results of the study show that the application of CTL can increase students' motivation, involvement, and understanding, as well as help them to develop good character in accordance with religious teachings. The application of Contextual Teaching and Learning (CTL) and axiological philosophy can create a more meaningful learning environment for students, so that children can more easily understand and apply the material that has been obtained.